2005
DOI: 10.1148/radiol.2361041278
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Chest Radiographs in Infants with Cough and Fever

Abstract: An understanding of the appearance of the infant chest radiograph requires an understanding of the anatomy and the physiologic, immunologic, and pathologic processes in the infant's chest. The authors describe the features of the infant chest that most influence the appearance of the chest radiograph in infants with cough and fever. They discuss why confusion sometimes occurs when radiology residents and general radiologists familiar with adult chest radiographs first evaluate the infant chest radiograph. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 5 publications
5
25
0
4
Order By: Relevance
“…Parahilar peribronchial infiltrates, hyperexpansion, segmental or lobar atelectasis, and hilar adenopathy have been common radiographic findings in the viral respiratory tract infections of children. The results of this study confirmed these findings (13,(16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Parahilar peribronchial infiltrates, hyperexpansion, segmental or lobar atelectasis, and hilar adenopathy have been common radiographic findings in the viral respiratory tract infections of children. The results of this study confirmed these findings (13,(16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 88%
“…The current study showed that about 60% of laboratory confirmed patients had normal radiographs. Among those with radiographic abnormalities, the most common finding was peribronchial increased opacities, similar to other reports of H1N1 in children (13) and other viral pneumonia in children (14,(16)(17)(18)(19)(20). Parahilar peribronchial infiltrates, hyperexpansion, segmental or lobar atelectasis, and hilar adenopathy have been common radiographic findings in the viral respiratory tract infections of children.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to pulmonary alveolar proteinosis, mosaic shadows are common in adult respiratory distress syndrome, bacterial pneumonia, AIP, and diffuse alveolar damage of usual interstitial pneumonia (UIP). Compared to desquamative interstitial pneumonia (DIP), UIP has older onset ages and obvious interlobular septal thickening shadows (Wittram et al, 2003;Bramson et al, 2005;Levine et al, 2007). However, children's ILD, especially children's infectious interstitial pneumonia, mostly led to the involvement of alveolar spaces, alveolar ducts, and small airways, whereas interlobular septal thickening was not common.…”
Section: Patchy Ground-glass Opacitiesmentioning
confidence: 99%
“…The intuitive reasons for bronchiectasis are a decrease in lung volume and fibrosis around lesions. Bramson et al (2005) indicated that bronchiectasis caused by pyogenic bacteria and viral infections often occurred in the two lower lungs. Due to the occlusion of its distal bronchi, bronchiectasis usually occurs in medium-sized bronchia.…”
Section: Bronchiectasismentioning
confidence: 99%
“…Z piśmiennictwa wynika, że okrą-głe zapalenie płuc jest częściej rozpoznawane u dzieci [4]. Jego przyczyną może być uwarunkowany rozwojem płuc brak dróg obocznych (porów Kohna, kanałów Lamberta), co ogranicza rozprzestrzenianie się zapalenia [5]. Czynniki etiologiczne okrągłego zapalenia płuc są typowe dla pozaszpitalnych zakażeń układu oddechowego.…”
Section: Dyskusjaunclassified